Family medicine practice in Saudi Arabia: The current situation and Proposed Strategic Directions Plan 2020 - Yahia M Al-Khaldi; Essam A Al-Ghamdi; Tariq I Al-Mogbil; Hesham I Al-Khashan (Wolters Kluwer Medknow Publications, 2017)
OBJECTIVES: The objectives of this study were to assess the current situation of the teaching and training of undergraduate and postgraduate programs in family medicine in KSA, assess the current practice of family medicine, and draw a roadmap to achieve Saudi vision 2020. MATERIALS AND METHODS: This study was conducted with the support and collaboration of the Primary Health Care Department of the Ministry of Health, Saudi Arabia, and World Health Organization (EMRO) in November 2015. Based on the literature review of previous studies conducted for similar purposes, relevant questionnaires were developed. These consisted of four forms, each of which was directed at a different authority to achieve the above-mentioned objectives. Data of all questionnaires were coded, entered, and analyzed using SPSS version 16. RESULTS: There are 2282 primary health-care centers (PHCCs), 60% of which are in rural areas. More than half of the PHCCs have a laboratory and more than one-third have a Radiology Department. Out of the 6107 physicians, 636 are family physicians (10%). All medical colleges have a family medicine department with a total staff of 170 medical teachers. Thirteen departments run family medicine courses of 4-8 weeks' duration for students. Fourteen colleges have internship programs in family medicine and four colleges have postgraduate centers for family medicine (27%). There are 95 training centers for Saudi Board (Saudi Board of Family Medicine [SBFM]) and 68 centers for Saudi Diploma (Saudi Diploma of Family Medicine [SDFM]). The total number of trainers was 241, while the total trainees were 756 in SBFM and 137 in SDFM. CONCLUSIONS: This survey showed that there is a shortage of qualified family physicians in all health sectors in Saudi Arabia as a result of the lack of a strategic plan for the training of family physicians. A national strategic plan with specific objectives and an explicit budget are necessary to deal with this shortage and improve the quality of health-care services at PHCCs.